Biomechanical Properties of Mouse Carotid Arteries With Diet-Induced Metabolic Syndrome and Aging - Gkousioudi, Anastasia; Yu, Xunjie; Ferruzzi, Jacopo; Qian, Juncheng; Wainford, Richard D.; Seta, Francesca; Zhang, Yanhang (Frontiers in Bioengineering and Biotechnology, 2022)
Metabolic syndrome increases the risk of cardiovascular diseases. Arteries gradually stiffen with aging; however, it can be worsened by the presence of conditions associated with metabolic syndrome. In this study, we investigated the combined effects of diet-induced metabolic syndrome and aging on the biomechanical properties of mouse common carotid arteries (CCA). Male mice at 2 months of age were fed a normal or a high fat and high sucrose (HFHS) diet for 2, 4 (young group), 8 (adult group) and 18-20 (old group) months. CCAs were excised and subjected to in vitro biaxial inflation-extension tests and the Cauchy stress-stretch relationships were determined in both the circumferential and longitudinal directions. The elastic energy storage of CCAs was obtained using a four-fiber family constitutive model, while the material stiffness in the circumferential and longitudinal directions was computed. Our study showed that aging is a dominant factor affecting arterial remodeling in the adult and old mice, to a similar extent, with stiffening manifested with a significantly reduced capability of energy storage by ~50% (p < 0.05) and decreases in material stiffness and stress (p < 0.05), regardless of diet. On the other hand, HFHS diet resulted in an accelerated arterial remodeling in the young group at pre-diabetic stage by affecting the circumferential material stiffness and stress (p < 0.05), which was eventually overshadowed by aging progression. These findings have important implications on the effects of metabolic syndrome on elastic arteries in the younger populations.